Family language policy in a transnational family living in Finland: multilingual repertoire, language practices, and child agency - Nenonen, Olga (Frontiers in Psychology, 2024)
Each multilingual transnational family is unique and thus deserves to be carefully studied in terms of its family language policy (FLP). Speaker-centered approaches can provide a deeper understanding of linguistic diversity in a multilingual setting. The studied Russian-Italian family is raising a multilingual boy (8:2) in Finland. The multilingual repertoire includes Russian, Italian, Finnish, English, and Hebrew. In this case-study, an ethnographic approach is used to explore the multilingual family repertoire by presenting their lived experiences and language practices. I discuss the FLP and child’s active role in shaping the family’s linguistic practices (child agency). The following methods were combined: semi-structured interviews, language background surveys, written diary entries, self-recordings of interactions in the family, and a language portrait that depicts the child’s multilingual repertoire. The interviews and other recordings were transcribed manually. The following research questions guided the study: (1) How do the family members describe their FLP? (2) How does the FLP evolve through everyday interactions (language practices)? (3) How does the child exercise his agency in the family setting? The results reveal that the family’s language practices follow predominantly an one person-one language (OPOL) strategy; consequently, the child speaks a different language with each parent. However, the analysis of the language ideologies reveals positive attitudes toward both multilingualism and all the languages in the family’s repertoire, which explains the multilingual practices having multiplicity and unexpectedness. FLP is shaping the family language practices. Evidence of language hierarchy can be explained by a number of family-external and family-internal social factors.